Analgesics Self-Medication Among Community In Cirebon District, Indonesia - Marfuati, Sri; Pratiwi, Witri; Khasanah, Uswatun (Jurnal Sehat Indonesia (JUSINDO), 2025)
Background: Self-medication with analgesics may cause inappropriate medication and potentially dangerous side effects. However, data on analgesic self-medication profiles in Cirebon, Indonesia, is still limited. Aims: This research aims to analyze the profile of self-medication with analgesics among the Cirebon District, Indonesia community. Methods An observational study with a cross-sectional approach was conducted in 5 pharmacies in the Cirebon District. The sample in this study was people who bought analgesics without a doctor's prescription at the pharmacy. Primary data were obtained through a questionnaire regarding sociodemographic characteristics, reasons for self-medication, and sources of information in choosing analgesics. Results: 470 respondents participated in this study, consisting of 35.96% male and 64.04% female. The majority of samples were 31-55 years old (54.9%), worked as housewives (36.60%), senior high school graduates (39.15%), married (74.68%), and had low income (60.43%). Only 13.83% of the sample has health insurance (private or national health insurance). Most of the samples performed self-medication with analgesic because they were used to doing it (34.25%). Most of the samples received information about analgesics they consumed from health workers (39.79%). Conclusion: Self-medication with analgesics among community in Cirebon Regency, Indonesia, is mainly carried out by low-income people because they are used to treating themselves. They get information about analgesics purchased from health workers. Prevention needs to be done through promotion and education to the public regarding the side effects of self-medicated analgesics so that they do not use them without consulting a doctor.